Attitudes towards Using E-Learning Platforms among Taiba University Students - AL-Ansari, Rofaydah Adnan (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify Tiaba University students' attitudes towards using E-learning platforms. It also aims to determine the differences that could be ascribed to scientific major in attitudes towards using E-learning platforms, and recognize the most preferred platform among the study participants. The study adopted the quasi-experimental design and the analytic descriptive approach. The study sample consisted of 126 students who were selected using purposive random sampling. To this end, a questionnaire has been constructed, containing 24 statements that covered positive and negative enhancement attitudes towards using E-learning platforms. The tools have been already ensured for reliability and validity, and has been administered during the first academic semester 2018-2019. The study has used different statistical methods such as frequencies, means, and standard deviation. Results demonstrated that the sample's attitudes were positive towards using the E-learning platforms. (M=23.2). However, results did not reveal any significant differences that could be ascribed to academic major. The participants viewed "Droob" platform as the most preferred one and ranked them first (72.22%), followed by Idrak platform (15.8%). The study has recommended the necessity of disseminating orientation among the students by adopting different technological methods, given that E-learning platforms become indispensable long-life learning and obtaining knowledge; the promising future for e-learning. The study has concluded with relative suggestions in the field.
Keywords: E-learning; open learning; instructional platforms; E-platforms